COMPARING PERCEPTIONS OF MRSA TRANSMISSION DYNAMICS IN DIVERSE HOSPITALS THROUGH PATIENT NARRATIVES (The Research of Medical Science Review, 2025)
Methicillin-intolerant Staphylococcus aureus (MRSA) is the most prevalent multidrug-resistant bacterium linked to healthcare. Although acute care hospitals (ACHs) and intermediate- and long-term care facilities (ILTCFs) are interconnected, little is known about how MRSA spreads between different healthcare settings. Methicillin-intolerant Serious issues are caused by Staphylococcus aureus (MRSA) worldwide. PCC addresses patients' psychological and emotional needs, which affect health outcomes, and increases adherence to infection prevention procedures. Better adherence to treatment plans and hygienic habits results from PCC's encouragement of patients to participate in their care actively. PCC in MRSA is neglected area, to fill this gap the research aims to understand the transmission dynamics of MRSA through patients narratives. the qualitative research design is adopted to explore MRSA effected patients perception. Grounded theory is used inductively and data was collected from MRSA-affected patients. the sampling is done by criterion sampling technique. The data is collected via semi-structured in-depth interviews with MRSA-infected patients. All the ethical guidelines and protocols are rigorously adhered. The data is analyzed by thematic analysis. Two major themes emerged after rigorous coding and chunking of the collected data. The results lead to a comprehensive model.